Pembelajaran Sastra melalui Cerita Bergambar Cerita Rakyat sebagai Upaya Penanaman Etika Siswa SD (Hiski Malang, 2021)
In literature learning especially oral learning, many teachers do not explore local folklore yet. Usually they used folklore from the other region which is well known, but the messages of value and ethics are not explored yet. Investment of ethical values to elementary school students is required. Interesting media should be used to implant ethics in elementary school students to make the learning process enjoyable. The subjects of the research are elementary school students and teachers, society leaders, village elders caretaker, and people of Boyolangu and Sendang districts, Tulungagung. Qualitative research is applied in this research. The results show that in Boyolangu and Sendang districts there were found 25 folklores consisting of 13 stories containing ethical value. They are the story of “Mbok Rondho Pendhadhapan”, “Terjadinya Dusun Glodhogan”, “Asal Usul Kesenian Tiban”, “Mbah Semare”, “Harimau Gembong”, “Terjadinya atau Lahirnya Angling Darmo”, “Joko Bodho”, “Astono Gedhong”, “Kera Ngujang”, “Roro Kembang Sore”, “Syeh Basarudin”, “Candi Omben Jago”, and “Punden Setono Badhong”. The stories have the ethical values, like friendliness, harmonius, cooperativeness, unity and integrity, strength, self-sacrificing.